Analysis on Spontaneous Combustion Characteristics of Adding Associated Sulfur Minerals in Coal. Issue 11 (2nd November 2019) - Jia, Hailin; Shen, Hedi; Zhai, Chenguang
ABSTRACT: In order to further study the influence of associated sulfur minerals on spontaneous combustion and ignition characteristics of coal, four coal samples with different sulfur contents were prepared by adding different sulfur minerals to raw coal, and through Thermogravimetric Analysis (TG) experiment, Differential Scanning Calorimeter (DSC) test and X-ray diffraction (XRD) analysis, the influence of associated sulfur minerals on spontaneous combustion and ignition characteristics of coal was studied. Experimental results show that with the increase of associated sulfur minerals, the characteristic temperature of coal decreases, while the oxygen absorption, flammability and incombustibility stability index increase gradually, indicating that the coal is more prone to spontaneous combustion after being mixed with the associated sulfur minerals. Based on Coats–Redfern method to calculate the activation energy of coal during combustion stage with different associated sulfur minerals in coal, the calculation shows that the activation energy of coal combustion stage decreases with the increase of the associated sulfur minerals in coal and makes it easily to burn. Through the XRD and DSC analysis of associated sulfur minerals, it is found that the main components of the associated sulfur minerals are melanterite and copiapite, which can react with water and oxygen at room temperature, and the exothermic reaction makes coal more prone to spontaneous combustion. The associated sulfur minerals are exothermic after 200°C and reach an exothermic peak at 565°C, which makes the activation energy of coal in combustion stage decrease and coal easily to burn.